Pengembangan E-Modul Berbasis Discovery Learning Berbantuan Canva pada Materi Reaksi Reduksi dan Oksidasi - Neneng Hadawang; Nursina Sya’bania; Kartini Rahman Nisa (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
The purpose of this research is to create e-module teaching materials with a discovery learning approach on the topic of oxidation-reduction reactions. These materials will be assessed for validity, practicality, and effectiveness in educational settings. This research uses the assurance development model which includes student character analysis, identification of learning objectives, selection of appropriate methods, media, and materials, utilization of media and materials in the learning process, active involvement of students, and evaluation phase. The e-module has successfully undergone a rigorous validation process conducted by a panel of validators and respected experts in the field. In addition, it has been thoroughly field tested to ensure that the resulting e-module is valid and effective, as well as practical in its application. The results showed that: 1) the assessment of media validity by media and material experts is included in the very valid category; 2) at the field trial stage involving 17 students of class X MIA 1 SMA Muhammadiyah Maumere, the class completeness rate was 81.3%. In addition, the electronic module (e-module) has been found to have a beneficial effect on student learning outcomes. Based on the descriptive analysis results, it can be concluded that the average student learning completeness rate is 87%. This indicates that e-modules used in an educational setting can be considered effective. The e-modules received positive responses from both students and teachers, indicating their practicality.